2021
DOI: 10.4322/acr.2021.330
|View full text |Cite|
|
Sign up to set email alerts
|

Fatal hemorrhage from peripheral varicose vein rupture

Abstract: Varix of the lower extremities is a common entity that eventually presents fatal outcome. Fatal massive bleeding due to rupture of a peripheral varicose vein is rare. The estimated incidence of these cases is 1/1000 autopsies. The case we present is unique among 26,054 autopsies performed in Milan from 1993 to 2020. It describes the investigations carried out in the suspicion of a non-natural event in an elderly woman. She was found dead at home with a large volume of blood near her feet that drained from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Moreover, even small varicose veins can lead to massive bleeding and fatal outcomes. One case reported that a 91‐year‐old woman, who was self‐sufficient and living alone, took oral antiplatelet drugs, and died of ruptured varicose veins at home 4 . Herein, we present a case of severe hemorrhage from rupturing of peripheral varicose vein that were formed due to previous surgery.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, even small varicose veins can lead to massive bleeding and fatal outcomes. One case reported that a 91‐year‐old woman, who was self‐sufficient and living alone, took oral antiplatelet drugs, and died of ruptured varicose veins at home 4 . Herein, we present a case of severe hemorrhage from rupturing of peripheral varicose vein that were formed due to previous surgery.…”
Section: Introductionmentioning
confidence: 94%
“…Currently, patients receiving anticoagulants are increasing. One paper reported that a 91-year-old, self-su cient, and lonely woman who took oral antiplatelet drugs died of ruptured Varicose Veins at home [4]. Even small varicose veins can lead to massive bleeding and fatal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Various contributing factors, such as geriatric skin fragility, use of anticoagulants and venous hyperpressure, consecutive to superficial venous insufficiency, deep venous insufficiency, or obstruction, further increase the risk of bleeding. 3,4 In this case report, we describe a case of recurrent bleeding associated with a varicose pearl nodule 1 on the dorsum of the right foot in a patient with superficial venous insufficiency.…”
mentioning
confidence: 99%
“…1 Consequently, even minor injuries can trigger dramatic hemorrhage. 3,4 Immediate external compression often falls short in controlling bleeding, but elevation of the leg to heart level can rapidly reduce venous pressure and halt bleeding. 1 Surgical ligation lacks sustained efficacy and can delay wound healing.…”
mentioning
confidence: 99%
See 1 more Smart Citation